Probiotic Lactobacillus rhamnosus GR-1 and Lactobacillus reuteri RC-14 exhibit strong antifungal effects against vulvovaginal candidiasis-causing Candida glabrata isolates - Chew, Shu Yih; Cheah, Yoke Kqueen; Seow, Heng Fong; Sandai, Doblin; Than, Leslie Thian Lung (The Society for Applied Microbiology, 2015)
Aims: This study investigates the antagonistic effects of the probiotic strains Lactobacillus rhamnosus GR-1 and Lactobacillus reuteri RC-14 against vulvovaginal candidiasis (VVC)-causing Candida glabrata. Methods and Results: Growth inhibitory activities of Lact. rhamnosus GR-1 and Lact. reuteri RC-14 strains against C. glabrata were demonstrated using a spot overlay assay and a plate-based microtitre assay. In addition, these probiotic lactobacilli strains also exhibited potent candidacidal activity against C. glabrata, as demonstrated by a LIVE/DEAD yeast viability assay performed using confocal laser scanning microscopy. The metabolic activities of all C. glabrata strains were completely shut down in response to the challenges by the probiotic lactobacilli strains. In addition, both probiotic lactobacilli strains exhibited strong autoaggregation and coaggregation phenotypes in the presence of C. glabrata, which indicate that these lactobacilli strains may exert their probiotic effects through the formation of aggregates and, thus the consequent prevention of colonization by C. glabrata. Conclusions: Probiotic Lact. rhamnosus GR-1 and Lact. reuteri RC-14 strains exhibited potent antagonistic activities against all of the tested C. glabrata strains. These lactobacilli exhibited antifungal effects, including those attributed to their aggregation abilities, and their presence caused the cessation of growth and eventual cell death of C. glabrata. Significance and Impact of the Study: This is the first study to report on the antagonistic effects of these probiotic lactobacilli strains against the non-Candida albicans Candida (NCAC) species C. glabrata.